Molecular clocks and the human condition: approaching their characterization in human physiology and disease. (September 2015) - Fitzgerald, G. A.; Yang, G.; Paschos, G. K.; Liang, X.; Skarke, C.
Abstract : Molecular clockworks knit together diverse biological networks and compelling evidence from model systems infers their importance in metabolism, immunological and cardiovascular function. Despite this and the diurnal variation in many aspects of human physiology and the phenotypic expression of disease, our understanding of the role and importance of clock function and dysfunction in humans is modest. There are tantalizing hints of connection across the translational divide and some correlative evidence of gene variation and human disease but most of what we know derives from forced desynchrony protocols in controlled environments. We now have the ability to monitor quantitatively ex vivo or in vivo the genome, metabolome, proteome and microbiome of humans in the wild. Combining this capability, with the power of mobile telephony and the evolution of remote sensing, affords a new opportunity for deep phenotyping, including the characterization of diurnal behaviour and the assessment of the impact of the clock on approved drug function.